Development of a superheated water chromatography method for the sustainable determination of preservatives in foods and cosmetics - Roberta La Tella; Danilo Donnarumma; Francesca Rigano; Paola Donato; Patrik Appelblad; Paola Dugo; Luigi Mondello; Alice Mondello (Green Analytical Chemistry)
The present research focused on the use of high temperatures to achieve fast separations in Liquid Chromatography (LC) and minimize the consumption of organic solvents. Particularly, superheated water was employed, by exploiting the decrease in dielectric constant of water when increasing the temperature. To realize this kind of application, the availability of LC columns resistant at high temperature is mandatory. Recently, porous graphitic carbon (PGC) columns have been proposed as stationary phases resistant up to 250 °C. Hardware modifications were also necessary to guarantee the efficient heating of the mobile phase prior of entering the column, as well as its rapid cooling before detection by photodiode array (PDA). Specifically, an LC system was interfaced to a GC oven, which hosted the LC column; to achieve a fast and efficient heating of the eluent coming from the autosampler prior to enter into the column, a pre-heating tube was interposed between the autosampler outlet and the column inlet. Instead, a cooling loop was connected between the column outlet and the PDA cell. A mixture of 1-nitroalkanes was used to evaluate the performance of the system in terms of dead volumes, band broadening and peak shape, as well as chromatographic efficiency and resolution. The use of higher temperatures allowed to perform analyses at higher flow rates in reduced analysis time and was also in terms of peak bandwidth resulting to increased efficiency for the most retained compound. Moreover, van't Hoff plots were obtained at different temperature, confirming that the most retained analyte greatly benefited of the temperature increase.The system was applied to the analysis of parabens in cosmetic and food products. The method combined eco-sustainable sample preparation with high-temperature LC separation on a PGC column and was fully validated in terms of linearity, precision, accuracy and detection and quantification limits. The developed method was critically evaluated by comparing the output of different metric tools implemented in the last decade for the quantitative assessment of the greenness.